Conjugate Effects on Steady Laminar Natural Convection Heat Transfer in Vertical Eccentric Annuli - El-Shaarawi, Maged A. I. (2005)
Combined conduction-free convection heat transfer in vertical eccentric annuli is numerically investigated using finite-difference technique. Numerical results are presented for a fluid of Prandtl number 0.7 in an annulus of radius ratio 0.5 and dimensionless eccentricity 0.5. The conjugation effect on the induced flow rate and the total heat absorbed in the annulus is presented for the case of one wall being isothermally heated while the other wall is kept at inlet fluid temperature. The conjugate effects are controlled by solid-fluid conductivity ratio, cylinder walls thickness and dimensionless channel height (i.e. Grashof number). Solid-fluid conductivity ratio is varied over a range that covers practical cases with commonly encountered inner and outer walls thickness. Values of conductivity ratio over which conjugate effect can be neglected have been obtained.